2007
DOI: 10.1021/ja0738881
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the Role of Water in Proline-Mediated Aldol Reactions

Abstract: A coherent mechanistic rationalization of the role of water in aldol reactions employing aromatic aldehydes shows that the intrinsic kinetic effect of water within the catalytic cycle is a suppression of reaction rate. The presence of water suppresses formation of key intermediates within the cycle as well as reversibly and irreversibly formed spectator species such as oxazolidinones and oxapyrrolizidines, respectively. The net effect on the observed productivity of the reaction will depend on the balance betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
160
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 257 publications
(175 citation statements)
references
References 19 publications
12
160
1
2
Order By: Relevance
“…11 However, our previous studies of the aldol reaction argue against this proposal. First, we showed clearly that the intrinsic kinetic effect of water is in fact to suppress, not to promote, the rate of the catalytic reaction [6]; second, our reported deuterium isotope effect of kH/kD ≈ 2 in the aldol reaction of eq 1c supports a role for the carboxyl proton in the ratedetermining enamine attack on the aldehyde 6. Further experimental studies to investigate the role of added base in the reactions of eq.…”
Section: Methodsmentioning
confidence: 66%
See 3 more Smart Citations
“…11 However, our previous studies of the aldol reaction argue against this proposal. First, we showed clearly that the intrinsic kinetic effect of water is in fact to suppress, not to promote, the rate of the catalytic reaction [6]; second, our reported deuterium isotope effect of kH/kD ≈ 2 in the aldol reaction of eq 1c supports a role for the carboxyl proton in the ratedetermining enamine attack on the aldehyde 6. Further experimental studies to investigate the role of added base in the reactions of eq.…”
Section: Methodsmentioning
confidence: 66%
“…Computational studies [3] have suggested a mechanistic analogy to reactions of aldolase enzymes [4]. Our recent work provided the first kinetic support for the enamine mechanism in aldol reactions and clarified the role of water on and off the catalytic cycle [5,6].…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Studies of the effect of water in the aldol condensation have been previously reported elsewhere. 38,39 They have demonstrated the role of water in the regeneration of active basic group (amines) at the expense of the inactive iminium form. This kind of observation is unlikely in our case as we don't expect to have amines in our carbons based on our investigations.…”
Section: Figure 17 Ft-ir Of C-500 C-700 and C-900mentioning
confidence: 99%